2021
DOI: 10.1200/jco.21.00612
|View full text |Cite|
|
Sign up to set email alerts
|

Lifileucel, a Tumor-Infiltrating Lymphocyte Therapy, in Metastatic Melanoma

Abstract: PURPOSE Effective treatment options are limited for patients with advanced (metastatic or unresectable) melanoma who progress after immune checkpoint inhibitors and targeted therapies. Adoptive cell therapy using tumor-infiltrating lymphocytes has demonstrated efficacy in advanced melanoma. Lifileucel is an autologous, centrally manufactured tumor-infiltrating lymphocyte product. METHODS We conducted a phase II open-label, single-arm, multicenter study in patients with advanced melanoma who had been previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
157
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(191 citation statements)
references
References 42 publications
0
157
0
Order By: Relevance
“…In a recent data analysis of clinical trials at our own institution, we have further concluded that disease progression after CPI therapy does not negate the ability for response to adoptive TIL therapy [88]. Even more recently the TIL-based ACT product, Lifileucel produced by Iovance Biotherapeutics, was shown to produce a durable response against metastatic melanoma in large cohorts of anti-PD-1 and PL-L1 refractory patients [89]. While CPI-resistance does not definitively nullify the success of TIL-based ACT, methods for optimizing treatment of this patient population should continue to be explored.…”
Section: The Effect Of Cpi-resistance On Til Therapymentioning
confidence: 93%
“…In a recent data analysis of clinical trials at our own institution, we have further concluded that disease progression after CPI therapy does not negate the ability for response to adoptive TIL therapy [88]. Even more recently the TIL-based ACT product, Lifileucel produced by Iovance Biotherapeutics, was shown to produce a durable response against metastatic melanoma in large cohorts of anti-PD-1 and PL-L1 refractory patients [89]. While CPI-resistance does not definitively nullify the success of TIL-based ACT, methods for optimizing treatment of this patient population should continue to be explored.…”
Section: The Effect Of Cpi-resistance On Til Therapymentioning
confidence: 93%
“…A recent meta-analysis by Dafni and colleagues found an ORR of 41% and a complete response rate of 12% in a total of 410 patient treated with TILs [130]. Recently, phase II results evaluating the efficacy of lifileucel (an autologous TIL product) in patients with advanced melanoma who had been previously treated with ICIs and BRAF/MEK-targeted agents observed an ORR of 36% and in patients refractory to anti-PD1/PD-L1 an ORR of 41% [132]. Additionally, a randomized phase III trial (NCT02278887) that is currently recruiting aims to show a better survival rate after TIL infusion compared to standard-of-care ipilimumab in patients with advanced-stage progressive melanoma in the first line of anti-PD1 treatment.…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 99%
“…Since immune checkpoint inhibitors (ICIs), such as ipilimumab (anti-CTLA-4 antibody), nivolumab, and pembrolizumab (both anti-PD-1 antibodies) achieved FDA approval, the landscape of immunotherapy for treating various solid tumors in recent years has changed [157]. Most clinical trials with ICIs in combination with cell therapy are combining tumor-infiltrating lymphocytes (TILs, e.g., lifileucel) [158], with one of the ICIs for treating melanoma, NSCLC, or head and neck cancer (NCT02027935, NCT03296137, NCT03638375, NCT03645928, NCT01993719). The clinical trials for treating solid tumors using CAR-T cells in combination with PD-1 blockade have been scheduled [159,160] and reviewed in [161].…”
Section: Immune Checkpoint Blockadementioning
confidence: 99%